Turkish Cypriot Community : Coping with the Turkish Lira Depreciation Shock - World Bank (World Bank, Washington, DC, 2020)
The Turkish lira (TL) has depreciated to an extent not seen since the 2001 crisis, reaching its lowest level in September 2018 (TL 6.37/US 1.00 dollar), losing 66 percent of its value against the US dollar since January 2018. This Regular Economic Report focuses on the likely impact of the depreciation on the Turkish Cypriot (TC) economy. Although the magnitude of the 2001 depreciation eventually turned out to be double the current depreciation, the reaction of the economy in 2001 offers useful insights into understanding the situation today. The report also discusses the financial situation of Local Communities Bodies (LCBs), whose budgets are highly dependent on transfers from the central administration. With the TL depreciation, fiscal pressures will arise at the central level, as with the local level, where the quality of service delivery is likely to be eroded as a result. To encourage spending reductions, the central administration could toughen its approach and reject budgets based on implausible revenue projections. It could encourage wage bill reductions by enforcing current limits on staffing and overall wage spending. It could also assist LCBs to improve the efficiency of services, such as water supply and solid waste management, by encouraging joint service arrangements among small LCBs. But much of the power to improve the situation lies with the LCBs themselves, as they have a considerable degree of fiscal autonomy despite the limits imposed by central regulations. They can increase basic tax rates up to the rate of inflation and impose higher valuations; and are also free to increase water tariffs (subject only to pro forma review) and the rate of various service charges within a range set by central regulation. Although their ability to reduce the number of civil servants is limited, they have considerable control over the numbers and wages of contracted staff and front-line service providers. The first section of this report discusses recent economic developments in the TCc with a focus on the likely economic impact of the TL depreciation. The second section assesses the state of the LCBs’.